A sensor-based approach to study sound perception in children. (2017) - Taffoni, Fabrizio; Perna, Leonardo Di; Formica, Domenico; Focaroli, Valentina; Keller, Flavio; Stefano, Nicola Di
In the present paper we describe an instrumented toy to study auditory preferences in young children. After brief considerations on the theoretical framework, the design of the mechanical, electronic and software components of the system is presented. The system allows for: (a) producing audio stimuli according to how children play with the toy; (b) assessing children's motor behaviour during the interaction. The device is provided with a sensor core enabling the assessment of manipulation in terms of angular displacement with errors lower than 1°. The laboratory validation is presented and discussed in details. Moreover, a pilot trial on two children aged 34 and 35 months is described and discussed. Results show the appropriateness of the technology to the experimental aims, and encourage research on methods based on the interaction between perception and action to investigate music preferences in young listeners.